From Labuhan Deli to Belawan: The Removal of Harbor in Medan during the Dutch Colonial Period of 1863-1942 - Suprayitno Suprayitno; Ratna Ratna; Rohani Ganie; Handoko Handoko (Budapest International Research and Critics University, 2020)
One of the effects of industrial development in plantation is the development in shipping and trade. Before the existence of plantations in East Sumatera, shipping and trade in Medan were centered at Labuhan Deli, as a river seaport. Periodically, shipping and trade activities at Labuhan Deli were in export and import from and to Malaya Peninsula (Penang and Malacca) and Singapore. The growth of plantations, of course, needed effective and efficient transportation. After the economy grew and was developed, Labuhan Deli as a river seaport was considered not effective and efficient anymore since ships with large cargoes could not sail on the river. Therefore, the Netherlands East Indies Government made a policy to build a new seaport which was located by the seaside in order to make loading and unloading goods easier. The Netherlands East Indies Government finally selected Belawan to be a new seaport for Medan. The research problems were as follows: how was the existence of Labuhan Deli by the policy of the Netherlands East Indies Government in moving the seaport to Belawan and what was the reason? How were the shipping and trade in Belawan seaport? These questions would be discussed in this research by using archives as the source and several writings published in Medan during the Dutch colonial period. The objective of the research was to describe the economic condition of the plantations which could change various aspects, specifically in shipping and trade. The research used historical research method which largely used archives from the Dutch colonial period, especially the statistics of shipping and trade, and the reports from BOW (Public Works Agency).